Improvement of purification system for roof water harvesting - Swatha V S (Department of land and water resources and conservation engineering, Kelappaji college of agricultural engineering and technology, 2015)
The severity of water scarcity and the need of water conservation, appropriate to the situation, are well understood facts and do not require any further elaboration. Knowing the potential of rooftop rainwater harvesting in Kerala state, the government has introduced legistation making rooftop rainwater harvesting mandatory for all newly constructed residential and commercial buildings. However, the roof water harvesting techniques is crippled with the inefficiency of the commonly employed sand and gravel purification system. The major deficiency of the system lies in the difficulty in cleaning of the filter media. Though studies have been initiated with alternative purification methods, it warrants further modification and improvisation. Keeping this in mind, this M.Tech research work has been taken up to find solutions to the purification issues of rooftop rainwater. The major focus of the work was to develop more efficient micro mesh filter in combination with a first flush system. To evaluate the performance of the filter and first flush, inflow and outflow of the roof water samples were analysed for pH, electrical conductivity, TDS, TSS, metal concentration and microbial parameters. In general, the pH, electrical conductivity and TDS of the roof water samples were within the drinking water standards for the different types of roofs tested. Micromesh purification reduced these quality parameters to further lower levels (10 to 20 percentage). Major TSS load was organic and its concentration was far beyond the permissible limit. Filtration with first flush system could reduce 88 percentage of the organic impurities. Metal and microbial concentrations of the roof water were within the permissible limits, the micromesh filtration could reduce their presence further by about 10 to15 percentage. There is further scope for improving the efficiency of mesh filters by adopting mesh sizes lower than 25 micron for which the discharge of the filter would not be a constraint, as has been revealed by the study.